Prenylflavonoids isolated from Epimedii Herba show inhibition activity against advanced glycation end-products - Nakashima, Keisuke; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi; Fujiwara, Yukio; Nagai, Ryoji; Ikeda, Tsuyoshi (Frontiers in Chemistry, 2024)
As inhibitors of advanced glycation end products (AGEs), such as pyridoxamine, significantly inhibit the development of retinopathy and neuropathy in rats with streptozotocininduced diabetes, treatment with AGE inhibitors is believed to be a potential strategy for the prevention of aging, age-related diseases, and lifestyle-related diseases, including diabetic complications. In the present study, the MeOH extract of Epimedii Herba (EH; aerial parts of Epimedium spp.) was found to inhibit the formation of N ε -(carboxymethyl)lysine (CML) and N ω -(carboxymethyl) arginine (CMA) during the incubation of collagen-derived gelatin with ribose. Materials and methods: EH was purchased from Uchida Wakan-yaku Co., and a MeOH extract was prepared. Several steps of column chromatography purified the extract. Each fraction was tested for inhibitory activity by ELISA using monoclonal antibodies for CML and CMA. Results: After activity-guided fractionation and purification by column chromatography, three new prenylflavonoids [named Koreanoside L (1), Koreanoside E1 (2), and Koreanoside E2 (3)] and 40 known compounds (4-43) were isolated from EH, and their inhibitory effects against CML and CMA formation were tested. Among these, epimedokoreanin B (8), epimedonin E (21), epicornunin B ( 22), and epicornunin F (24) inhibited the formation of both CML and CMA, with epimedokoreanin B (8) having the most potent inhibitory effect among the isolated compounds. To obtain the structureactivity relationships of 8, the phenolic hydroxy groups of 8 were methylated by trimethylsilyldiazomethane to afford the partially and completely methylated compounds of 8. Prenyl derivatives of propolis (artepillin C, baccharin, and drupanin) were used in the assay. Discussion: As only 8 showed significant activity among these compounds, the catechol group of the B ring and the two prenyl groups attached to the flavanone skeleton were essential for activity. These data suggest that 8 could prevent the clinical complications of diabetes and age-related diseases by inhibiting AGEs.